2016
DOI: 10.1371/journal.pone.0146312
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Lactobacillus rhamnosus GG Supplementation Improves the Mucosal Barrier Function in the Intestine of Weaned Piglets Challenged by Porcine Rotavirus

Abstract: Lactobacillus rhamnosus GG (LGG) has been regarded as a safe probiotic strain. The aim of this study was to investigate whether dietary LGG supplementation could alleviate diarrhea via improving jejunal mucosal barrier function in the weaned piglets challenged by RV, and further analyze the potential roles for apoptosis of jejunal mucosal cells and intestinal microbiota. A total of 24 crossbred barrows weaned at 21 d of age were assigned randomly to 1 of 2 diets: the basal diet and LGG supplementing diet. On d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
64
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 60 publications
8
64
0
1
Order By: Relevance
“…ETEC decreased transepithelial resistance (TEER) and increased IL-8 expression, and this effect could be prevented by both pre-incubation and simultaneous addition with E. faecium for up to 4 h Lodemann et al 2015). Similarly, another E. faecium strain (HDRsEf1), as well as its cell-free supernatant, could attenuate ETEC K88-induced IL-8 secretion and TEER decrease in IPEC-J2 cells (Tian et al 2016).…”
Section: Probiotics Used In Pig Intestinal Cells Challenged With Etecmentioning
confidence: 99%
See 1 more Smart Citation
“…ETEC decreased transepithelial resistance (TEER) and increased IL-8 expression, and this effect could be prevented by both pre-incubation and simultaneous addition with E. faecium for up to 4 h Lodemann et al 2015). Similarly, another E. faecium strain (HDRsEf1), as well as its cell-free supernatant, could attenuate ETEC K88-induced IL-8 secretion and TEER decrease in IPEC-J2 cells (Tian et al 2016).…”
Section: Probiotics Used In Pig Intestinal Cells Challenged With Etecmentioning
confidence: 99%
“…Several L. reuteri strains have been used in pig trials, in particular, the I5007 strain has been shown to have beneficial effects on performance and growth, prevention of diarrhea, altered gut microbiota, and immunomodulation (reviewed by Hou et al 2015). Finally, LGG supplementation could alleviate the diarrhea in RV-challenged weaned piglets through inhibition of virus multiplication, as well as improvement of intestinal mucosal barrier function and of intestinal microbiota composition (Mao et al 2016). …”
Section: Prevention Of Diarrheamentioning
confidence: 99%
“…During RVs infections in weaned pigs, there is evidence of disruption of the barrier function as evidenced by the decreased villus height and crypt depth, lower levels of IgA, IL-4, and mucin 1 as well a reduced transcription of ZO-1, occludin, and Bcl-2 in jejunal mucosa (47). Some of these effects have been partially associated with alterations of transforming growth factor (TGF)-β production (48).…”
Section: Beneficial Effects Of Immunobiotics In Rotavirus Infectionmentioning
confidence: 99%
“…The alteration of intestinal morphology due to colistin supplementation could also be associated with a deleterious effect on commensal bacteria playing a role in gut development (Sommer and Bäckhed, 2013). Yin et al (2008) reported that colistin supplementation during the 2 weeks after weaning altered the E. coli population in the jejunum and ileum, but also that of Lactobacilli colonies, which are recognised for their beneficial effect on the mucosal structure of the intestine (Mao et al, 2016). The observed reduction of villus height in the jejunum of non-infected piglets supplemented with colistin may be explained by an alteration of microbial populations in the intestine, with a deleterious effect on mucosal development after weaning.…”
mentioning
confidence: 99%
“…Huang et al (2004) reported that Lactobacilli improved microbial balance in the digestive tract of piglets during the first 2 weeks after weaning and resulted in fewer cases of diarrhoea and an increase in growth. Lactobacilli strains also play a role in improving the mucosal barrier function and reducing mucosal injury caused by pathogenic microorganisms (Mao et al, 2016). Therefore, a reduced incidence of diarrhoea, enhancement of intestinal morphology and a trend to increased nutrient digestibility in Chlorella supplemented pigs may result from a decrease in oxidative stress and local inflammation, but also from a positive effect on microbial balance in the gut.…”
mentioning
confidence: 99%